Influence of irregularities in the electrolyte on the cathodic protection of steel: A numerical and experimental study. Issue 12 (21st May 2013) - Montoya, R.; Nagel, V.; Galván, J. C.; Bastidas, J. M.
Abstract This paper shows how the last algebraic matricial form can be obtained when the finite element method is used to approximate the potential distribution of a cathodic protection system that includes low conductivity irregularities in the electrolyte away from, close to and directly on the cathode. In order to study the influence of the resistivity of these irregularities on the possibilities of steel protection, five conductivities were analysed. The numerical results, validated with COMSOL® Multiphysics, show the importance of considering irregularities in the domain in order to prevent systems from becoming unprotected. The experimental data agrees with the theoretical data.